Optimization of process parameters for Si lateral PIN photodiode - Menon P.S.; Kalthom Tasirin S.; Ahmad I.; Fazlili Abdullah S. (2023)
This paper is about four optimization factors of process parameters, namely the intrinsic region length, photoabsorption layer thickness, the incident optical power and the bias voltage in a Si lateral pin-photodiode so as to obtain high frequency response and responsivity. Optimization of these parameters is based on Taguchi optimization method. In terms of simulation for the fabrication and device electrical characterization, ATHENA and ATLAS software from Silvaco Int. were used respectively. The identified factors have three best levels which give different combination based on L9 orthogonal array by Taguchi optimization method. In order to find the optimum factors and levels, signal-to-noise ratios (SNR) of larger-the-better (LTB) was applied. The analysis showed that the entire identified factors gave significant effect on the optical properties of the Si lateral pin-photodiode. It is revealed that the best result for responsivity and frequency response after the optimization approaches were 0.62A/W and 13.1 GHz respectively which respond to the optimized value for intrinsic region length of 6 ?m, photoabsorption layer thickness of 50 ?m, incident optical power of 1 mW/cm2 and bias voltage of 3 V. As a conclusion, the optimum solution in achieving the desired high speed photodiode was successfully predicted using Taguchi optimization method. IDOSI Publications, 2013.